Sol-gel synthesis, characterisation and photocatalytic activity of pure, W-, Ag- and W/Ag co-doped TiO2 nanopowders - Tobaldi, D. M.
Tungsten, silver and tungsten/silver co-doped titania nanopowders were synthesised via an aqueous sol-gel method. The size distribution and zeta potential of the starting sols were determined via photon correlation spectroscopy (PCS). The dried gels were thermally treated at two different temperatures, and the occurrence of amorphous phase was assessed using the combined Rietveld-RIR X-ray powder diffraction method. A systematic study of the optical properties of the powders was made with diffuse reflectance spectroscopy (DRS), and the energy band gaps were calculated using the differential reflectance method; while their morphology was investigated using electron microscopy analysis (TEM). The photocatalytic activity of the samples was assessed in liquid-solid phase, under UVA-light and visible-light irradiation, monitoring the degradation of an organic dye. The influence of the phase composition, optical properties, dimensions, and specific surface area of the powders on the photocatalytic activity was thoroughly discussed. (C) 2012 Elsevier B.V. All rights reserved.